Kepemimpinan Perempuan Dalam Pendidikan Islam - Siti Kafidhoh (Kopertais Wilayah I DKI Jakarta dan Banten, 2019)
Women's Leadership in Islamic Education (Study on Role of Umi Waheeda in Managing Al-Ashriyyah Nurul Iman Islamic Boarding School Parung Bogor). This research found that the most dominant female leadership style shown by Umi Waheeda in managing Pesantren Nurul Iman is the Melati Style, with the main characteristic of simple, polite and wise leadership in all its members. This is also reinforced by the nature of leadership shown by Umi Waheeda with the nature of the mother and iron maden. Umi Waheeda shows maternal traits in directing employees, and has always been a strong and visionary women leader.Another interesting thing found in this study, in the perspective of Umi Waheeda employees, it shows the uniqueness of being a leader so that it becomes a characteristic of female leaders who distinguishes from other leaders including: 1) Umi Waheeda as a strong leader woman, 2) productive leader, by developing various social entrepreneurs; 3) Independent Free Education Initiators, in the sense that without relying on donations from other institutions; 4) The Trusty Leader, by establishing a non-profit institution to provide thousands of orphans and underprivileged people in terms of education, health, and free residence with istiqomah; 5) A progressive leader, provides periodic and continuous progress for the Al-Ashriyyah pesantren Nurul Iman.